2022
DOI: 10.1177/01655515221114452
|View full text |Cite
|
Sign up to set email alerts
|

A Tailored Approach: A model for literature searching in complex systematic reviews

Abstract: Our previous work identified that nine leading guidance documents for seven different types of systematic review advocated the same process of literature searching. We defined and illustrated this process and we named it ‘the Conventional Approach’. The Conventional Approach appears to meet the needs of researchers undertaking literature searches for systematic reviews of clinical interventions. In this article, we report a new and alternate process model of literature searching called ‘A Tailored Approach’. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…Of these, we excluded 100 references due to various reasons, mostly wrong study aim, and finally included 47 studies 26,27–69,70–72 (Figure 1). For three of the studies, 42,71,35 we found related documents (erratum, 73 doctoral thesis, 74 and evidence summary 75 ), yielding a total of 50 reports, two of which were conference posters 51,46 . Twenty‐six reports (52%) were included from the results of the bibliographic database search and 24 (48%) from the supplementary search results (one from web searching, 14 from backward CT, six from forward CT, and three from contacting experts).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, we excluded 100 references due to various reasons, mostly wrong study aim, and finally included 47 studies 26,27–69,70–72 (Figure 1). For three of the studies, 42,71,35 we found related documents (erratum, 73 doctoral thesis, 74 and evidence summary 75 ), yielding a total of 50 reports, two of which were conference posters 51,46 . Twenty‐six reports (52%) were included from the results of the bibliographic database search and 24 (48%) from the supplementary search results (one from web searching, 14 from backward CT, six from forward CT, and three from contacting experts).…”
Section: Resultsmentioning
confidence: 99%
“…38 RCTs were included in the EGM. The database Ageline returned the most RCTs (Tan et al, 2006 ), followed by CINAHL (Chonody, 2015 ) and then MEDLINE (Cooper et al, 2022 ). Only 10 of the included RCTs were retrieved from the CENTRAL database.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, social science databases are more likely to be hosted by platforms that are not designed for systematic searching (Bethel & Rogers, 2014 ). A recent study advocates for a more tailored approach to searching in complex systematic reviews (Cooper et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, we excluded 171 references due to various reasons, mostly wrong study aim, and finally included 47 studies 26-72 (Figure 1). For three of the studies, 41,71,34 we found related documents (erratum, 73 doctoral thesis, 74 and evidence summary 75 ), yielding a total of 50 reports, two of which were conference posters. 50,45 Twenty-six reports (52%) were included from the results of the bibliographic database search and 24 (48%) from the supplementary search results (one from web searching, 14 from backward CT, six from forward CT, and three from contacting experts).…”
Section: Resultsmentioning
confidence: 99%